The Challenges in the Development of Diabetes Prevention and Care Models in Low-Income Settings - Karachaliou, Feneli; Simatos, George; Simatou, Aristofania (Frontiers in Endocrinology, 2020)
In low- and middle-income countries (LMICs), the burden of non-communicable diseases (NCDs) such as diabetes is rapidly rising against the existing burden of communicable diseases. Diabetic patients living in low-income communities face unique challenges related to lack of awareness, difficulty in accessing health care systems and medications and consequently failure in achieving optimal diabetes management and preventing complications. Effective diabetes prevention and care models could help reduce the rising burden by standardizing guidelines for prevention and management, improving access to care, engaging community and peers, increasing the training of professionals and patients and using the newest technology in the management of the disease. In this paper we review the latest research and evidence on effective models of diabetes prevention and diabetes care delivery in low income settings. We also provide existing evidence relating to the effectiveness of these models in low resource contexts with the aim to highlight characteristics and strengths that make their implementation successful and long-lasting